Promoting Gender Equality: A Systematic Review of Interventions - Guthridge, Michaela; Kirkman, Maggie; Penovic, Tania; Giummarra, Melita J. (Social justice research, 2022)
More than four decades have passed since the United Nation’s Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) was adopted. Now is an opportune time to consider whether the interventions seeking to realise CEDAW’s aspirations have brought us closer to achieving gender equality. This systematic review aimed to identify and synthesise evidence for the effectiveness of social justice, cognitive, or behaviour-change interventions that sought to reduce gender inequality, gender bias, or discrimination against women or girls. Interventions could be implemented in any context, with any mode of delivery and duration, if they measured gender equity or discrimination outcomes, and were published in English in peer-reviewed journals. Papers on violence against women and sexuality were not eligible. Seventy-eight papers reporting qualitative (n = 36), quantitative (n = 23), and multi-methods (n = 19) research projects met the eligibility criteria after screening 7,832 citations identified from psycINFO, ProQuest, Scopus searches, reference lists and expert recommendations. Findings were synthesised narratively. Improved gender inclusion was the most frequently reported change (n = 39), particularly for education and media interventions. Fifty percent of interventions measuring social change in gender equality did not achieve beneficial effects. Most gender mainstreaming interventions had only partial beneficial effects on outcomes, calling into question their efficacy in practice. Twenty-eight interventions used education and awareness-raising strategies, which also predominantly had only partial beneficial effects. Overall research quality was low to moderate, and the key findings created doubt that interventions to date have achieved meaningful change. Interventions may not have achieved macrolevel change because they did not explicitly address meso and micro change. We conclude with a summary of the evidence for key determinants of the promotion of gender equality, including a call to address men’s emotional responses (micro) in the process of achieving gender equality (micro/meso/macrolevels).